Medication adherence and concordance among diabetes patient: a mini review - Saidi, Sanisah; Sabran, Najwatul Madihah; Mohd Razali, Rossheilawani; Mohd Salleh, Fatin Emaneina; Jamaludin, Thandar Soe Sumaiyah (East African Scholars Publisher, Kenya, 2019)
Diabetes mellitus places an immense burden on the individuals living with the condition, their families and the overall health care system despite the advances in the treatment of diabetes mellitus over the years. Thus, this review aimed to search the literatures on the adherence and concordance of diabetes patient’s tolerance in taking their medication. Five articles were selected for this min review. Finding showed that the factors influence on the nonadherence and concordance towards medication among diabetes patients are high expenses of medication, age factor, belief in traditional medication and dietary modification. It is important for the nurses and other health care providers to remind the patient and always assess their understanding as both sides have come to a shared agreement about therapeutic goals.